KEMAMPUAN EFEKTIVITAS SEKAM PADI (Oryza sativa) SEBAGAI ADSORBEN TERHADAP PENYERAPAN LOGAM BERAT TIMBAL - Maria Priska Yati; Yusriani Sapta Dewi (JURNAL TECHLINK, 2022)
The environment is said to be a polluted area, if there is a change in the standards of environmental quality standards which include, water, soil and air. This can happen by several factors, one of which is mining activities. Rice husk is a form of agricultural waste which is a "waste" from rice processing which has the potential as an adsorbent to absorb lead ions (Pb). In this study, rice husks were prepared with two treatments: non-activating and with 30% NaOH activation after being heated in a furnace at a temperature of 400 oC for 1 hour then the adsorbent was sieved with particles that passed through a 40 mesh sieve. The adsorbent was used to absorb 200 ml of Pb ions with an adsorbent weight of 5 grams, where the adsorption process was carried out in 2 contact times, 60 minutes and 120 minutes and tested in the laboratory. The adsorption process was obtained, the optimum was at a contact time of 120 minutes and the treatment was activated, with an average percentage of 94%.